Hubungan antara Pengembangan Agrowisata Subak dengan Modal Sosial pada Subak Jatiluwih Tabanan - NI MADE SUKRAENI ASIH; NYOMAN SUTJIPTA; I MADE SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
The Relation between Agrotourism’s Development toward SocialCapital Condition of Jatuliwuh Subak, TabananFarming sector in Bali strongly related to Subak system because Subak controls theirrigation system. Subak also sets the patterns and schedule of the cropping. Subakin Bali started to develop as Agrotourism since UNESCO officially announceSubak as one of the World Heritage. This acknowledgement could be an effectivemedia to promote Subak Jatiluwih and attract tourist to come. The number of thevisitors keeps arising from years. In 2012, there were 97,909 visitors, 101,560 in2013 and 165,158 in 2014. The purpose of this research is to know the relationbetween agrotourism’s developments toward social capital condition in JatiluwihSubak, Tabanan. In order to know if there is any relation between agrotourismdevelopments toward Subak’s social capital, this research use rank spearmancorrelation test and descriptive analysis for processing the data. The result of therank spearman correlation test shows that there is no relation between thedevelopments of agrotourism toward social capital condition. While from thedescriptive analysis that is showed in percentage, social capital’s percentage reach76.72%. It means that social capital stands in “good” level. This percentage showsthat the development of agrotourism does not have any relation toward socialcapital condition.